Eight Dogs, or "Hakkenden" : Part One-An Ill-Considered Jest - Takizawa, Bakin, 1767-1848 (Book collections on Project MUSE., 2021)
"A translation of the first fourteen chapters of the Japanese novel Nansō Satomi Hakkenden (1814-1842) by Kyokutei Bakin (1767-1848)"--